2018
DOI: 10.1038/s41434-018-0040-9
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-mediated delivery for non-viral mRNA vaccines

Abstract: mRNA is increasingly being recognized as a promising alternative to pDNA in gene vaccinations. Only recently, owing to the needs of cancer immunotherapies, has the biomaterials/gene delivery community begun to develop new biomaterial strategies for immunomodulation. Here, we report a novel way to use implantable porous scaffolds as a local gene delivery depot to enhance mRNA vaccine immunization in vitro, and in vivo when compared with conventional bolus injections. We first evaluated transfection efficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 43 publications
1
54
0
1
Order By: Relevance
“…We found that both carriers and scaffold served important roles in the improvement of local transfection in vivo 2 days post‐injection. Previous results from scaffold‐released mRNA vaccines demonstrated that dendritic cells are recruited into the scaffold, uptake mRNA lipoplexes, then migrate to draining lymph nodes for T cell stimulation to initiate an adaptive immune response …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that both carriers and scaffold served important roles in the improvement of local transfection in vivo 2 days post‐injection. Previous results from scaffold‐released mRNA vaccines demonstrated that dendritic cells are recruited into the scaffold, uptake mRNA lipoplexes, then migrate to draining lymph nodes for T cell stimulation to initiate an adaptive immune response …”
Section: Discussionmentioning
confidence: 99%
“…Previous results from scaffold-released mRNA vaccines demonstrated that dendritic cells are recruited into the scaffold, uptake mRNA lipoplexes, then migrate to draining lymph nodes for T cell stimulation to initiate an adaptive immune response. [41] Various nanoparticle systems have been developed for maintaining mRNA stability and bioactivity. In this study, an injectable scaffold platform was designed specifically for mRNA loading and it was combined with the standard mRNA lipoplex nanoparticle technology for mRNA vaccine delivery in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Messenger RNA vaccines are composed of one or more nucleic acids encoding for a single or multiple vaccine antigen candidates, formulated in a delivery vehicle and then directly delivered into the host cell. These delivery vehicles include lipid-and protein-based molecules, as well as various types of polymeric scaffolding [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Additional new modified nanoparticles are currently being investigated, such as polyplexes, nanoplexes and porous polymer scaffold-mediated delivery (116)(117)(118)(119)(120)(121)(122). Although great advances have been achieved in the development of delivery tools, the ideal platform maybe a combination of different mRNA delivery tools and more efforts in understanding mechanism of action might be required.…”
Section: Rna Vaccines In the Prevention Of Infectious Diseasementioning
confidence: 99%